Trichinella spiralis Calreticulin Binds Human Complement C1q As an Immune Evasion Strategy - Zhao, Limei; Shao, Shuai; Chen, Yi; Sun, Ximeng; Sun, Ran; Huang, Jingjing; Zhan, Bin; Zhu, Xinping (Frontiers in Immunology, 2017)
As a multicellular parasitic nematode, Trichinella spiralis regulates host immune responses by producing a variety of immunomodulatory molecules to escape from host immune attack, but the mechanisms underlying the immune evasion are not well understood. Here, we identified that T. spiralis calreticulin (Ts-CRT), a Ca2+ binding protein, facilitated T. spiralis immune evasion by interacting with the first component of human classical complement pathway, C1q. In the present study, Ts-CRT was found to be expressed on the surface of different developmental stages of T. spiralis as well as in the secreted products of adult and muscle larval worms. Functional analysis identified that Ts-CRT was able to bind to human C1q, resulting in the inhibition of C1q-initiated complement classical activation pathway reflected by reduced C4/C3 generation and C1q-dependent lysis of antibody-sensitized sheep erythrocytes. Moreover, recombinant Ts-CRT (rTs-CRT) binding to C1q suppressed C1q-induced THP-1-derived macrophages chemotaxis and reduced monocyte-macrophages release of reactive oxygen intermediates (ROIs). Blocking of Ts-CRT on the surface of newborn larvae (NBL) of T. spiralis with anti-Ts-CRT antibody increased the C1q-mediated adherence of monocyte-macrophages to larvae and impaired larval infectivity. All of these results suggest that T. spiralis-expressed Ts-CRT plays important roles in immune evasion and survival in host mostly by directly binding to host complement C1q, which not only reduces C1q-mediated activation of classical complement pathway but also inhibits the C1q-induced non-complement activation of macrophages.